Correlation Between Protamine-2 and miRNA-122 in Sperm from Heroin-addicted Men: A Case-Control Study - Nazmara, Zohreh; Najafi, Mohammad; Movahedin, Mansoureh; Zandiyeh, Zahra; Shirinbayan, Peymaneh; Asgari, Hamid reza; Roshanpajouh, Mohsen; Maki, Chad B.; Bashiri, Zahra; Koruji, Morteza (Urology Journal, 2020)
Purpose: Recreational use of illicit drugs is one of the main factors affecting male fertility. However, the mechanisms of heroin smoke-associated damage to mature spermatozoa are still completely unknown. The aim of this study was to concomitantly examine the levels of protamine-2 gene and protein concentrations, the amount of miRNA-122 in seminal plasma and semen analysis findings in heroin-addicted men. Materials and Methods: In a case control study, twenty-four fertile men that lacked any recreational drug abuse were considered as the healthy group, and 24 addicted men who used only heroin for at least four months were selected as the addicted group. Semen samples were gathered by masturbation after 2 - 5 days of sexual abstinence. Following the preparation of a semen analysis by computer-assisted sperm analysis according to WHO (2010), the level of protamine-2 gene expression in sperm and miRNA-122 in seminal plasma was measured using real-time sqPCR. Also, protamine-2 protein concentrations were quantified by nuclear protein extraction, SDS-Page and western blotting. Results: Among the studied variables, body mass index (27.75±0.88 vs. 22.30±0.36, p=0.001), seminal pH (7.79±0.06 vs. 7.58±0.06, p=0.003), white blood cell count in semen (1.69±0.41 vs. 8.61±1.73, p=0.001), motility (65.51±2.57 vs. 41.96±3.58, p=0.001) and survival rate (87.41±1.00 vs. 71.50±4.59, p=0.002) of sperm cells was significantly different between the healthy and addicted groups. In addition, the levels of protamine-2 gene and protein expression in the addicted group (0.05±0.02 and 0.10±0.02, respectively) were significantly lower than the healthy group (3.59±0.94 and 0.27±0.06, respectively) (p=0.002 and p=0.017, respectively). Seminal miRNA-122 levels in addicted men (3.51±0.73) were statistically higher than in healthy men (1.52±0.54) (p=0.034). However, there were some significant relationship between the studied parameters and addiction (p<0.05). Conclusion: This is one study on human infertility that evaluates the effects of heroin on protamine deficiency and seminal small RNAs expression levels. Heroin abuse may lead to male infertility by causing leukocytospermia, asthenozoospermia, protamine deficiency, and seminal plasma miRNA profile alteration.